The power athlete - Longhurst, J. C.; Stebbins, C. L. (Cardiology Clinics, 1997)
A number of normal daily and athletic activities require isometric or static exercise. Sports such as weight lifting and other high-resistance activities are used by power athletes to gain strength and skeletal muscle bulk. Static exercise, the predominant activity used in power training, significantly increases blood pressure, heart rate, myocardial contractility, and cardiac output. These changes occur in response to central neural irradiation, called central command, as well as a reflex originating from statically contracting muscle. Studies have demonstrated that blood pressure appears to be the regulated variable, presumably because the increased pressure provides blood flow into muscles whose arterial inflow is reduced as a result of increases in intramuscular pressure created by contraction. Thus, static exercise is characterized by a pressure load on the heart and can be differentiated from the hemodynamic response to dynamic (isotonic) exercise, which involves a volume load to the heart. Physical training with static exercise (i.e., power training) leads to concentric cardiac (particularly left ventricular) hypertrophy, whereas training with dynamic exercise leads to eccentric hypertrophy. The magnitude of cardiac hypertrophy is much less in athletes training with static than dynamic exercise. Neither systolic nor diastolic function is altered by the hypertrophic process associated with static exercise training. Many of the energy requirements for static exercise, particularly during more severe levels of exercise, are met by anaerobic glycolysis because the contracting muscle becomes comes deprived of blood flow. Power athletes, training with repetitive static exercise, derive little benefit from an increase in oxygen transport capacity, so that maximal oxygen consumption is increased only minimally or not at all. Peripheral cardiovascular adaptations also can occur in response to training with static exercise. Although the studies are controversial, these adaptations include modest decreases in resting blood pressure, reduced increases in blood pressure and sympathetic nerve activity during a given workload, enhanced baroreflex function, increases in muscle capillary-to-fiber ratio, possible improvements in lipid and lipoprotein profiles, and increases in glucose and insulin responsiveness. Some of these adaptations can occur in cardiac or hypertensive patients with no concomitant cardiovascular complications. In both healthy individuals and those with cardiovascular disease, the manner in which resistance training is performed may dictate the extent to which these adjustments take place. Specifically, training that involves frequent repetitions of moderate weight (and hence contains dynamic components) seems to produce the most beneficial results.